Perbaikan Efisiensi Gudang pada Paris Superstore Kotamobagu dengan Pendekatan Lean Logistic - Maulana, Adryan Nanda; Komaro, Mumu; Larutama, Wiku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Warehouses play a crucial role in the trading business, serving as temporary storage facilities and order fulfillment centers. Paris Superstore Kotamobagu faces several issues, such as product damage due to stockpiling, rodent infestations, and a suboptimal warehouse layout. One solution to address these problems is the implementation of the lean logistics method. This study employs a qualitative descriptive approach with a case study strategy to explore waste-related issues. Identified wastes include waiting, inventory, motion, and defects. The 5 Why’s analysis revealed the root causes of these problems. The implementation of the 5S method resulted in improved time efficiency, better stock management, and reduced product damage.